IMPROVING WRITING SKILLS OF SHORT STORIES THROUGH THE QUANTUM LEARNING METHOD IN SMAN 1 TIRTAJAYA KARAWANG CLASS XI IPA 2 STUDENTS - Fauzya Hayatun Nupus; Agustus Gentur Supriyadi; Teti Sobari (JLER (Journal of Language Education Research), 2019)
This Classroom Action Research aims to describe the application of the quantum learning method to improve students' skills in writing short stories. The subjects in this study were students of class XI IPA 2 Tirtajaya 1 Public High School, amounting to 40 people. Based on the results of this study, it can be concluded that the application of the quantum learning method can improve writing skills. The application of the quantum learning method in writing learning gets a positive response from students. Students can write short stories with the right steps. Therefore, this researcher suggests applying the quantum learning method, as one of the learning methods, in other language subjects in general and in Indonesian language learning.